Determinants of choice behaviour of Islamic investment products in Malaysia - Hanudin Amin; Dwi Suhartanto; Muhammad Ali; Mohd Fahmi Ghazali; Rizal Hamid; Dzuljastri Abdul Razak (Emerald Group Publishing Limited, 2022)
In spite of the increasing number of Islamic banks offering Islamic investment products, there is, as yet, little academic research on this topic and the consumer acceptance of the products is not yet understood fully. To help in bridging this gap, this study aims to assess the determinants of choice behaviour of Islamic investment products in Malaysia. Using the Theory of Consumption Value (TCV) as a baseline theory, data are obtained from 460 bank customers who intend to invest in the products. The results of this study show that emotional value, epistemic value, conditional value, functional value and social value are significantly related to the choice behaviour of Islamic investment products. Three concerns were found in this study. Firstly, the geographies of this study are narrowed down to bank customers who were resided in specific areas in East Malaysia. Secondly, the authors used the TCV on a particular focus of Islamic banking products. Future studies should address these issues accordingly for improved application and generalisation. Thirdly, some reliability issues were identified in composite reliability values and the related future studies are expected to strengthen the research design to extend the findings at best. The results are helpful for practitioners to develop new business models of Islamic investment products in Malaysia. Originality/value: This study provides meaningful insights for theory building of choice behaviour in the context of Islamic investment products, where the TCV comes into play.